Environmental Management Accounting and Sustainable Banking Performance: A Systematic Literature Review of Green Innovation, Contingency Factors, and Organizational Effectiveness - Herlina (LPPM STIE Kasih Bangsa, 2026)
This study presents a qualitative Systematic Literature Review (SLR) examining the role of Environmental Management Accounting (EMA) in enhancing Sustainable Banking Performance through Green Innovation, Contingency Factors, and Organizational Effectiveness. Following the PRISMA 2020 guidelines, peer reviewed studies published in reputable international journals were systematically identified, screened, and synthesized. The review reveals that EMA has evolved into a strategic management accounting system that supports environmental decision-making, resource efficiency, ESG implementation, and sustainable finance. The findings indicate that Green Innovation strengthens the effectiveness of EMA by fostering sustainable financial products and operational improvements, while Contingency Factors including organizational size, environmental strategy, regulatory pressure, and managerial commitment influence successful EMA implementation. Furthermore, Organizational Effectiveness mediates the relationship between EMA and Sustainable Banking Performance by improving strategic capability, innovation, and operational efficiency. This review contributes an integrated conceptual understanding of sustainable banking and provides practical implications for managers, regulators, and policymakers seeking to advance sustainability-oriented banking practices.